Idea of Europe in inter-war Romania; Ideea de Europa în România interbelică - Mihai Sebe (European Institute of Romania, 2010)
The present paper intends to examine the evolution of the European idea in inter-war Romania. On this occasion, I try to have a synthetic presentation of Romanian currents and intellectual evolutions, a history of that idea in inter-war political and intellectual environments. Romanian élites prove to be connected to the evolutions at the European level, offering solutions and professionally commenting the proposals presented. The Romanian conception on the united Europe remarks itself through the great importance given to the political factor - the European states should be united, equal and have the frontiers guaranteed. We have a qualitative evolution that starts with the idea of regional associations culminating with the idea of a united Europe based upon the proposal of Aristide Briand. By the end of the 1930s and mid-40s, the accent is set upon the idea of a European Economic Community, partially based upon the German ideas of World War II.
Keywords: 330; history of the idea of Europe; inter-war period; European Union; extremism; political thinking; communism; social-democracy; Europäische Integration; Wirtschaftsintegration; Ideologie; Rumänien